Health education strategies for literacy of vulnerable populations in Primary Health Care: a scoping review - Risia Raphaely do Rêgo Barros Melo; Saulo Watanabe Costa; Paula Daniella de Abreu; Gabriella Barreto Soares (Espaço para a Saúde - Revista de Saúde Pública do Paraná, 2026)
Health literacy (HL) is important for health promotion and the reduction of inequities. This study aimed to map health education strategies used in Primary Health Care (PHC) for the development of HL in vulnerable populations. This is a scoping review conducted according to the Joanna Briggs Institute, searching ten databases and grey literature up to August 2024. Of the 215 studies identified, 12 comprised the final sample. The strategies included individual counseling, educational groups, workshops, peer education, telephone follow-up, use of digital technologies, audiovisual resources, games, and simulations. Interventions focused on strengthening the functional and interactive dimensions of HL predominated, with results related to increased knowledge, autonomy, health communication, and self-care. It is concluded that PHC constitutes a strategic space for the development of HL, although interventions focused on critical literacy, social participation, and addressing health inequities are still scarce.